2005
DOI: 10.1287/moor.1040.0130
|View full text |Cite
|
Sign up to set email alerts
|

The Continuous Mixing Polyhedron

Abstract: We analyze the polyhedral structure of the sets PCMIX = {(s, r, z) ∈ R × R+n × Zn ∣ s + rj + zj ≥ fj, j = 1, …, n} and P+CMIX = PCMIX ∩ {s ≥ 0}. The set P+CMIX is a natural generalization of the mixing set studied by Pochet and Wolsey [15, 16] and Günlük and Pochet [8] and recently has been introduced by Miller and Wolsey [12]. We introduce a new class of valid inequalities that has proven to be sufficient for describing conv(PCMIX). We give an extended formulation of size O(n) × O(n2) variables and constraint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…It follows from their work that the internal description of conv(X CM IX ) has exponential size. Van Vyve [48] has provided a new more compact extended formulation that only involves O(n) additional variables, and has shown that the separation problem in the original space can be solved by flow techniques.…”
Section: Continuous Mixing Setmentioning
confidence: 99%
See 1 more Smart Citation
“…It follows from their work that the internal description of conv(X CM IX ) has exponential size. Van Vyve [48] has provided a new more compact extended formulation that only involves O(n) additional variables, and has shown that the separation problem in the original space can be solved by flow techniques.…”
Section: Continuous Mixing Setmentioning
confidence: 99%
“…That is, continuous variables are expressed as a combination of few auxiliary integer variables, thus reducing the original problem to a pure integer one. This approach has been particularly successful in several problems arising in lot-sizing [42], [30], [40], [48], [14] (see [43] for a survey).…”
Section: Variable Discretizationmentioning
confidence: 99%
“…Let Q be the polyhedron on the space of the variables {(x i , µ i ℓ ), i ∈ N, ℓ ∈ K ∪{0}} defined by the inequalities (10)-(15) corresponding to inequalities (16), (17) Proof: Theorem 5 shows that every minimal face of Q contains a vector (x,μ) with integral µ. So the same holds for Q I , which is a face of Q.…”
Section: Ray Of the Polyhedron Which Is The Convex Hull Of The Vectormentioning
confidence: 95%
“…An extended formulation for conv(CM IX) which is compact was given by Miller and Wolsey [13]. Later Van Vyve [16] gave a more compact extended formulation and a linear inequality description of conv(CM IX) in the original space.…”
Section: The Continuous Mixing Setmentioning
confidence: 99%
See 1 more Smart Citation